STUDY OF THE LANDFORMS OF THE IBICUÍ RIVER BASIN WITH USE OF TOPOGRAPHIC POSITION INDEX - Trentin, Romario; Robaina, Luís Eduardo de Souza (Revista Brasileira de Geomorfologia, 2018)
The Topographic Position Index (TPI) is an algorithm which calculates the difference of the elevation between a central pixel ( and the mean of the elevation of its surroundings () surroundings defined by of a radius determined by the user. The study was developed in the Ibicuí Basin, located in the west of Rio Grande do Sul, with a surface area of 46,602.58 km², with a perimeter of 1,268.76 km and an 8th order hierarchy. The TPI analysis associated with inclination determined 08 landforms elements in the BHRI: flat area elements, top elements identified as flat and wavy, springs, slopes and the footslopes and channel elements that can be closed or opened.